2004
DOI: 10.1002/mabi.200300084
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Polythioesters

Abstract: This feature article describes the current knowledge on biosynthesis of polythioesters (PTEs), which are exclusively accumulated by microorganisms capable to synthesize the well-known polyhydroxyalkanoates (PHAs). Two bacterial PTE biosynthesis systems are discussed, both are depending on the cultivation conditions and appropriate feeding regimes. The first system comprises the production of PTE copolymers by Ralstonia eutropha, and the second system has been established in recombinant Escherichia coli to prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
40
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 44 publications
1
40
0
Order By: Relevance
“…This clearly demonstrated that WS/ DGAT is capable of catalyzing not only oxo ester bond formation but also thio ester bond formation. In analogy, bacterial PHA synthases catalyzing the biosynthesis of PHA are also capable of utilizing the sulfur analogues of their natural substrates, which are short-and medium-chain-length 3-hydroxyacyl-CoAs, resulting in polythioester biosynthesis (15). Furthermore, it was recently shown that lipases are able to biosynthesize thio wax esters (28) and polythioesters, respectively (8).…”
Section: Discussionmentioning
confidence: 99%
“…This clearly demonstrated that WS/ DGAT is capable of catalyzing not only oxo ester bond formation but also thio ester bond formation. In analogy, bacterial PHA synthases catalyzing the biosynthesis of PHA are also capable of utilizing the sulfur analogues of their natural substrates, which are short-and medium-chain-length 3-hydroxyacyl-CoAs, resulting in polythioester biosynthesis (15). Furthermore, it was recently shown that lipases are able to biosynthesize thio wax esters (28) and polythioesters, respectively (8).…”
Section: Discussionmentioning
confidence: 99%
“…The molecular masses of PHA polymers can range from 50 to 1,000 kDa or even above, and they may exhibit variable physical properties according to their monomer composition (244,245). The lack of specificity of PHA synthases is further underlined by their ability to synthesize polythioesters (PTE) by generating thioester bonds between 3-mercaptopropionic acid or other thiolic compounds (246,247).…”
Section: Pha Synthasesmentioning
confidence: 99%
“…PTE homopolymers are synthesized by applying the artificial BPEC pathway in the recombinant Escherichia coli strain JM109(pBPP1) (7). Therefore, 3MP, 3-mercaptobutyrate (3MB), or 3-mercaptovalerate (3MV) is applied as a precursor substrate (7,8). Only recently, the production of PTE homopolymers in Advenella mimigardefordensis DPN7…”
mentioning
confidence: 99%